Design of wireless remote monitoring and control system based on radio modem - TAN Changse (Gong-kuang zidonghua, 2015)
In view of problems of large investment, long communication distance, low data transmission rate and small transmission quantity existed in monitoring and control system of water supply well and sewage treatment with cable communication mode, a wireless remote monitoring and control system based on radio modem was designed. The system uses radio modem as the transmission medium of monitoring data, video information and voice signals, and ensures the reliability and real-time performance of data transmission; uses configuration software as the monitoring software, so as to realize stable operation of the remote monitoring and control system.